Krytyka koncepcji przyspieszania wzrostu dochodu narodowego - Mielcarek, Jarosław (Wydział Prawa i Administracji UAM, 1984)
The article elaborates some elements of a growth model for centralized economy. A modified version of extended reproduction and resulting consequences related to formation of basic macroeconomic relations in the economy became a point of departure for the present study. Next, conditions of dynamic equilibrium were formulated concerning proportions of productive capital distribution between two sectors, distribution of material accumulation, rate of profit, rate of material accumulation, rate of increase of material accumulation and a rate of balanced growth. Transformed formula of Kalecki, account being made for demand factors adopted the identical shape to the last value cited. On the grounds of the said results, the author is answering a query: what are the processes to take place in the centralized economy in the Center increases a rate of growth of national income by enlarging the portion of accumulation in it having stable prices, nominal wages, the solution chosen by M. Kalecki at no technical progress and zero growth of work efficiency is to be excluded. Ascertainments on sources of financing material accumulation and economic growth under condition of economic equilibrium and disequilibrium allowed to analyse consequences of accelerating growth under conditions of disequilibrium. Several formulae are quoted to present relations between a rate of investments and price levels and the rate of compulsory savings and the coefficient of deficite of production of consumption goods. In addition, to underscore the specifics of relations mechanism between investments and savings in the centralized system comparisons were made in that scope with the classical and Keynsian theories.
Some elements of a growth model for centralized economy